A simple Cascade Method for Mixed Noise Removal - Shukur, Nidhal (Iraqi Journal of Science, 2024)
Images are usually corrupted by type of noise called "mixed noise ", traditionalmethods do not give good results with the mixed noise (impulse with Gaussiannoise) .In this paper a Simple Cascade Method (SCM) will be applied for mixednoise removal (Gaussian plus impulse noise) and compare it’s performance withresults that acquired when using the alpha trimmed mean filter and wavelet inseparately. The performances are evaluated in terms of Mean Squane Error (MSE)and Peak Signal to Noise Ratio (PSNR).